2021
DOI: 10.1177/18479804211035190
|View full text |Cite
|
Sign up to set email alerts
|

Parameters and properties for the preparation of Cu nanocolloids containing polyvinyl alcohol using the electrical spark discharge method

Abstract: Through the use of an electric discharge machine, this study performed the electrical spark discharge method in deionised water under normal temperature and pressure for Cu nanocolloid (CuNC) preparation. The CuNCs had a zeta potential of 12.3 mV, indicating poor suspension stability. The suspension stability was effectively increased (zeta potential 32.5 mV) through the addition of polyvinyl alcohol (PVA) to form PVA-containing CuNCs PVA/CuNCs. Next, the following pulse-width modulation (Ton:Toff) parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…e PVAcontaining CuNCs PVA/CuNCs were formed by adding polyvinyl alcohol (PVA), which effectively improved the suspension stability (zeta potential of 32.5 mV). When T on : T off is set to 30 : 30 s, the preparation efficiency is the best, and the suspension stability is also the best [1]. Loan et al investigated the cellular effects of platinum nanoparticles (PtNP) and platinum nanocolloids (PtNC) on mouse leukemia Raw 264.7 cells.…”
Section: Related Workmentioning
confidence: 99%
“…e PVAcontaining CuNCs PVA/CuNCs were formed by adding polyvinyl alcohol (PVA), which effectively improved the suspension stability (zeta potential of 32.5 mV). When T on : T off is set to 30 : 30 s, the preparation efficiency is the best, and the suspension stability is also the best [1]. Loan et al investigated the cellular effects of platinum nanoparticles (PtNP) and platinum nanocolloids (PtNC) on mouse leukemia Raw 264.7 cells.…”
Section: Related Workmentioning
confidence: 99%
“…As shown in Figure a, AMP on the surface of the gold core resulted in a lower negative charge (−4.82 ± 0.23 mV) for the AuNCs, and the surface charge of PVA was found to be −3.41 ± 0.18 mV. With the addition of less than 10 μM PVA, the zeta potential of the AuNCs increased from 4.82 to 22.1 mV, indicating that a stable dispersive system was formed due to electrostatic repulsion; a steric effect between the nanoparticles provided and allowed resistance to the surface attraction between the particles . Therefore, colloids of PVA-coated AuNCs were formed in the assembly process.…”
Section: Resultsmentioning
confidence: 93%
“…With the addition of less than 10 μM PVA, the zeta potential of the AuNCs increased from 4.82 to 22.1 mV, indicating that a stable dispersive system was formed due to electrostatic repulsion; a steric effect between the nanoparticles provided and allowed resistance to the surface attraction between the particles. 39 Therefore, colloids of PVA-coated AuNCs were formed in the assembly process. However, the electrokinetic potential values gradually decreased in the presence of PVA (>10 μM), which indicated that the stable space of nanoparticles in the spherical colloid was destroyed and the concentration of free counterions in the solution decreased; thus, the overall viscosity of the solution increased.…”
Section: The Intrinsic Assembly Mechanism Between Auncs and Pvamentioning
confidence: 99%
“…Nanometal colloids, such as nanogold, nanosilver, nano-copper, nano-aluminum, and nano-titanium, can be made with any method able to conduct electricity using an EDM [ 26 , 27 , 28 , 29 , 30 ]. Nanosilver colloids have been applied in biomedical research, and silver ions can resist bacteria growth.…”
Section: Methodsmentioning
confidence: 99%